P130 A RARE CASE OF LARGE POST INFARCTION LEFT VENTRICULAR PSEUDOANEURYSM UNDERGOING CONSERVATIVE MANAGEMENT. (18th May 2022) - Di Saverio, M; Massacesi, C; Rolando, M; Iadanza Lanzaro, B; Marrangoni, A; Gregori, G; Napoletano, C; Marini, L; Gennarelli, A
Abstract: Introduction: Left ventricular pseudoaneurysm is a rare complication of myocardial infarction and its natural history is still unclear. Non invasive imaging improves detection ability and differential diagnosis with aneurysm. We present the case of large post infarction left ventricular pseudoaneurysm undergoing conservative management. Case Report: A 81–years–old woman presented to emergency room complaining dyspnea and epigastric and right hemithoracic pain. Her past medical history included: chronic coronary syndrome, already undergoing CABG; recent inferior STEMI complicated with complete AVB, with ineffective RCA reperfusion attempt and bicameral pacemaker implantation; Paroxysmal AF in antithrombotic prophylaxis with DOAC. The ECG showed sinus tachycardia, HR 114 bpm, electro–induced ventricular complexes. Objectively, fine bilateral basal crackles were detected. Chest x–ray showed pulmonary congestion. The echocardiographic examination revealed: left ventricle with eccentric remodeling and severe depression of the contractile function (EF 35%), coarse neochamber in communication with the basal segment of the lower wall (D: 6.4 cm x 4.9 cm). The narrow neck, with a ratio <0.5 between inlet orifice diameter / neochamber diameter, suggested pseudoaneurysm. Working diagnosis of NSTEMI–ACS was made (usTnT peak: 344 pg / mL, NV: 0–15 pg / mL) complicated by heart failure. Progressive improvement in compensation was achieved through diuretic therapy. To improve diagnostic definition, cardio–synchronized chest CT with contrast medium was performed. The examination confirmed the voluminous neochamber, consistent with pseudoaneurysm, in correspondence with the mid–basal segments of the lower and inferior septal wall, with thinned walls and mass effect on the great cardiac vein, and highlighted the patency of the bypasses. The venous graft to OM was 5 mm distant from the posterior sternal surface. The case was discussed collectively in Heart Team, due to the high operative risk, the surgical option was rejected and a decision was made for conservative therapy. It was titled beta–blocker, ranolazine was introduced, heart failure therapy was implemented, introducing ARNI. The patient was discharged at home and is in follow–up at the outpatient clinic for heart failure. One month after discharge, she is in NYHA functional class II and she is asymptomatic for angor. The pseudoaneurysmatic dimensions are unchanged on echocardiographic control.